Mitochondrial Fusion Machinery Specifically Involved in Energy Deprivation-Induced Autophagy - Wu, Choufei; Yao, Weijing; Kai, Wenwen; Liu, Weikang; Wang, Wenlve; Li, Shuzhen; Chen, Yingcong; Wu, Xiaoyong; Wang, Liefeng; Li, Ying; Tong, Jingjing; Qian, Jing; et al. (Frontiers in Cell and Developmental Biology, 2020)
Mitochondria are highly dynamic organelles, which can form a network in cells through fusion, fission and tubulation. Its morphology is closely related to the function of mitochondria. The damaged mitochondria can be removed by mitophagy. However, the relationship between mitochondrial morphology and non-selective autophagy is not fully understood. We found that mitochondrial fusion machinery, not fission and tubulation machinery, is essential for energy deprivation-induced autophagy. In response to glucose starvation, the deletion of mitochondrial fusion proteins severely impaired the association of Atg1 with Atg13, and then affected the recruitment of Atg1 and other autophagic proteins to PAS (phagophore assembly site). Furthermore, the deletion of fusion proteins blocks mitochondrial respiration, the binding of Snf1-Mec1, the phosphorylation of Mec1 by Snf1, and the dissociation of Mec1 from mitochondria under prolonged starvation. We propose that mitochondrial fusion machinery regulates energy deprivation-induced autophagy through maintaining mitochondrial respiration.